Application of a NIR device for precision feeding in dairy farms: effect on metabolic conditions and milk production - Fiorenzo Piccioli-Cappelli (Italian Journal of Animal Science, 2019)
Forages dry matter (DM) could vary among batches and in particular when silages are fed. These variations could modify nutrients composition of total mixed ration and affect cows performance. The aim of this study was to evaluate the effect of application of a precision feeding system (PFS) based on a near infra-red scanner, on metabolic conditions and milk yield in lactating dairy cows. The study was performed in 7 farms where PFS was installed on feed mixer to perform a weight-adjustment of DM measured in real time on feeds. A cross-over (14 weeks periods) was applied, PFS was switched on (PF-ON) in three herds and off in the other four (PF-OFF) during 1st period, and vice versa in 2nd period. At the end of two periods, in each herd 7 early and 7 mid lactation cows, for a total of 196 cows, were checked for: blood parameters, milk yield and composition. During the study deviation of DM of target diet (calculated on amount of feed in recipe and applying the DM determined in laboratory) and diets really distributed to cows tended to be lower with PF-ON vs. PF-OFF (0.06 vs 0.12 kg, p = .12). In early lactating cows, lower blood urea (4.63 vs 4.88 mmol/L, p = .115) indicated a better feed protein utilisation in PF-ON vs. PF-OFF. Milk yield and composition were not affected. The use of PFS meliorated the consistency of TMR, which could determine a better efficiency of nutrients utilisation and a reduction of production costs.Highlights Near infra-red (NIR) technology can be advantageously applied at farm level within a precision feeding system for dairy cows. The system allowed a more constant daily supply of nutrients with a reduction of metabolic alterations and a higher efficiency of feed protein utilisation. Utilization of NIR technology at farm level can be economically sustainable.